Crossmodal correspondences between visual features and tastes in preschoolers: an exploratory study - Meng, Xianwei; Chen, Na; Ishida, Junya; Watanabe, Katsumi; Murakami, Taro (Frontiers in Psychology, 2023)
Introduction: Adults possess a natural inclination to associate sensory cues derived from distinct modalities, such as the pairing of sweet with pink. However, studies exploring crossmodal correspondences in children, particularly in the sensory pairing of visual features and tastes, are scant, leaving unanswered questions regarding the developmental trajectory of crossmodal correspondences. The present study investigates whether Japanese preschool children demonstrate specific biases in shape–color, shape–taste, and color–taste associations. Methods: In a series of in-person experiments, 92 children between 3 to 6 years of age completed matching tasks utilizing paper stimuli. Results: Children exhibit crossmodal correspondences in shape-color (circle-red and asymmetrical star-yellow), shape–taste (triangle-salty and circle-sweet), and color–taste (yellow-sour, black-bitter, and pink-sweet) associations. Moreover, children’s choices are not influenced by their individual preferences. Discussion: The crossmodal correspondences observed in this study have been observed in previous research on adults from the same (Japanese) culture, although adults showed more crossmodal correspondences than the children in this study (e.g., pink-circle, triangle-sour, green-bitter). Thus, while some crossmodal correspondences emerge during childhood, others may require additional time to develop, thereby highlighting the importance of understanding the cognitive mechanisms underlying crossmodal correspondences from an ontogenic perspective.